-7*(m-5)=4(4-m)+1

Simple and best practice solution for -7*(m-5)=4(4-m)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7*(m-5)=4(4-m)+1 equation:



-7(m-5)=4(4-m)+1
We move all terms to the left:
-7(m-5)-(4(4-m)+1)=0
We add all the numbers together, and all the variables
-7(m-5)-(4(-1m+4)+1)=0
We multiply parentheses
-7m-(4(-1m+4)+1)+35=0
We calculate terms in parentheses: -(4(-1m+4)+1), so:
4(-1m+4)+1
We multiply parentheses
-4m+16+1
We add all the numbers together, and all the variables
-4m+17
Back to the equation:
-(-4m+17)
We get rid of parentheses
-7m+4m-17+35=0
We add all the numbers together, and all the variables
-3m+18=0
We move all terms containing m to the left, all other terms to the right
-3m=-18
m=-18/-3
m=+6

See similar equations:

| b=50+(15+6) | | (5)/(6)x+4=19 | | 143/a=13 | | m-1.6/3.2=10 | | 2x+7+3x-13=7 | | 2x-16+2x-21=7 | | 156/13=z | | 12=11w-7w | | 156/13=x | | 7(x-7)+8x=-94 | | 4x-5/7=-7 | | -10m-3=77 | | -5(7v+4)=155 | | 7(1-3n)=112 | | 3.75x+3.7=1.7+1.6x | | 11z+6=8z+10 | | -7x-6(x-1)=-98 | | -24=4/3(x-15) | | 10^3x+1=43 | | 4c*6=2 | | 3x(8-2x)=0 | | 109​=k10​ | | (q+4)^2=196 | | 2.4x+1.35-0.04x=3.71x-10.8 | | 38+7k=8+(k+4) | | 6(4-3m)=168 | | 0.4x+0.9=0.24x+0.54 | | 2x+29+9=x+26 | | 259=185-x | | 4+3b=11b+12 | | x+7(x+4)=92 | | 5(x-2)=105x-2=10 |

Equations solver categories